Enseñanza de guión: un desafío académico - Teichmann, Rosa Matilde (2017)
The article reflects on the questioning about our object of study and teaching within the subject Guion I in Facultad de Bellas Artes. We also intend to form script writers, who can see further from the canon, considering the script as a narrative and aesthetic structure of audiovisual creation and as an object of constant transformation. At the same time, the challenge of the subject is to train students/ researchers / artists, facing reality with a critical approach and a transforming view of it.